A 17 GHz molecular rectifier - J. Trasobares (Nature Portfolio, 2016)
Molecular electronics holds promise to overcome scaling limits of conventional technologies, but is currently limited to low frequency operation. Here, Trasobares et al. show radio frequencies of up to 17.8 GHz in a molecular diode based on ferrocenyl undecanethiol self-assembled monolayers on gold nanodots.